Quelques dimensions politiques de l’écotourisme : l’attractivité de la nature n’est pas « naturelle » - Bruno Sarrasin (Études Caribéennes)
This article explores the reasons why the social, political and economic stakeholders choose to promote natural resources by means of and for ecotourism. It hypothesizes that the attractiveness of nature-based ecotourism is not revenue neutral - that is, those involved in promoting this approach do so out of self interest. Through its close relationship with biodiversity, the dimensions of which are not appreciated by all, ecotourism is a vehicle for development and consolidation of power, particularly that of "éco-power", that is say those stakeholders who have information on the state of natural resources and the solutions available to them.